(untitled) (International journal of artificial intelligence, 2026)
The process of creating a character in puppet theater is not limited to movements and speech on stage; it also involves interactive communication with the audience. The image of each hero is shaped based on the creative vision of the director and the actor, and through their movements, facial expressions, and speech style, it influences the audience's perception. Interaction with the audience changes the dynamics of the performance and strengthens the emotional connection between the stage and the viewers. This process reveals the unique features of puppet theater and provides an opportunity to elevate art and creative experience to a new level.